Herba Ecliptae Protects against Hydroxyl Radical‐induced Damages to DNA and Mesenchymal Stem Cells via Antioxidant Mechanism. Issue 10 (26th June 2014) - Han, Lu; Sun, Chengjie; Lin, Jian; Li, Fei; Li, Xican; Wu, Zisheng; Liu, Chengping; Bai, Ye; Mai, Wenqiong; Chen, Dongfeng
Abstract Herba Ecliptae (HE) is a typical Chinese herbal medicine used in China for 1500 years. In the study, HE was extracted by various solvents to prepare five HE extracts. They were observed to possess a protective effect against ×OH‐induced DNA damage, and scavenging effects on ×OH radical, ×O2− radical, DPPH×(1, 1‐diphenyl‐2‐picrylhydrazyl) radical, and ABTS×+ (2, 2′‐azino‐bis(3‐ethyl‐benzothiazoline‐6‐sulfonic acid) radical, and reduce Cu2+ ion. The contents of total phenolics and wedelolactone in five extracts were determined respectively using Folin‐Ciocalteu method and HPLC method. To identify which chemical component can be responsible for its effects, the correlation graphs between chemical contents and antioxidant abilities (1/IC50 values) were plotted to calculate correlation coefficients (R values). Finally, MTT assay revealed that two HE extracts could effectively protect mesenchymal stem cells (MSCs) against ×OH‐induced damage at 3‐30 μg/mL. On the basis of mechanistic analysis, we concluded that: (i) HE can effectively protect against ×OH‐induced damages to DNA and MSCs, thereby HE may have a therapeutic potential in MSCs transplantation or prevention of many diseases; (ii) the effects can be mainly attributed to total phenolics (R = 0.678) especially wedelolactone (R = 0.618); (iii) they exert antioxidant action via hydrogen atom transfer (HAT) and sequential electron proton transfer (SEPT) mechanisms.